Accidental swallowing of orthodontic expansion appliance key - Monini, Andre da Costa [UNESP]; Martins Maia, Luiz Guilherme [UNESP]; Jacob, Helder Baldi [UNESP]; Gandini Júnior, Luiz Gonzaga [UNESP] (Mosby-elsevier, 2011)
Ingestion of a foreign object, including a dental object, can lead to a trip to the emergency room. This article describes the accidental swallowing of a key that was used to activate a rapid maxillary expander. An orthodontic patient swallowed the key while trying to activate the appliance at home. The object's trajectory was followed on radiographs until it was eliminated. Possible clinical complications, legal implications of this situation, and practices for prevention are described. (Am J Orthod Dentofacial Orthop 2011;140:266-8)